KEKUATAN BENDING KOMPOSIT CLAY DIPERKUAT DENGAN ALUMINA UNTUK APLIKASI FIRE BRICK - Hamzah, Muhammad Sadat; Sam, Alimuddin (Jurnal MEKANIKAL, 2013)
This study aims to utilize clay obtained from the Central Sulawesi which has 27.445 % Al2O3 composition ; SiO2 50.251 %, 9.331 % Fe2O3 ; Na2O 4.041 %, 3.263 % CaO ; K2O 3.733 %, MgO 2.40 %, 0.168 % TiO2 as a matrix clay -reinforced alumina composite . Alumina powder is a ceramic material that is hard and resistant to high temperatures . Alumina powder as much as 0, 15, 30, 45 , and 60 % weight fraction of powder mixed with clay that has been calcined at a temperature of 800 ° C for 30 minutes ( size ≤ 74 lm ) . Each mixture was stirred using a mixer brands Stuart Scientific for 2 hours . A mixture of clay and alumina powders were uniaxial dikompaksi with 50 MPa pressure and then sintered at atmospheric environment with a temperature of 1000 ° C. 1100 ° C , 1200 ° C and 1300 ° C. Testing is done is the density and bending strength . The test results showed that with increasing weight fraction of alumina and sintering temperature will increase the relative density and bending strength , but if the increase is not accompanied by the weight fraction of alumina sintering temperature rise will decrease the value of the relative density and bending strength . Value of the relative density and bending strength of the composite obtained at the highest weight fraction of 60 % alumina and sintering temperature of 1300 ° C , respectively, 72.28 % and 62.14 MPa